Perinatal Derivatives: Where Do We Stand? A Roadmap of the Human Placenta and Consensus for Tissue and Cell Nomenclature - Silini, Antonietta Rosa; Di Pietro, Roberta; Lang-Olip, Ingrid; Alviano, Francesco; Banerjee, Asmita; Basile, Mariangela; Borutinskaite, Veronika; Eissner, Günther; Gellhaus, Alexandra; Giebel, Bernd; Huang, Yong-Can; Janev, Aleksandar; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Progress in the understanding of the biology of perinatal tissues has contributed to the breakthrough revelation of the therapeutic effects of perinatal derivatives (PnD), namely birth-associated tissues, cells, and secreted factors. The significant knowledge acquired in the past two decades, along with the increasing interest in perinatal derivatives, fuels an urgent need for the precise identification of PnD and the establishment of updated consensus criteria policies for their characterization. The aim of this review is not to go into detail on preclinical or clinical trials, but rather Herein we address specific issues that are relevant for the definition/characterization of perinatal cells, starting from an understanding of the development of the human placenta, its structure, and the different cell populations that can be isolated from the different perinatal tissues. We describe where the cells are located within the placenta and their cell morphology and phenotype. We also propose nomenclature for the cell populations and derivatives discussed herein. This review is a joint effort from the COST SPRINT Action (CA17116), which broadly aims at approaching consensus for different aspects of PnD research, such as providing inputs for future standards for the processing and in vitro characterization and clinical application of PnD.